(untitled) (Physical Education, Health and Social Sciences, 2026)
Soil microbial communities serve as the primary biological drivers of carbon sequestration and nutrient cycling in terrestrial ecosystems, where soil organic carbon (SOC) stocks represent the largest terrestrial carbon reservoir approximately three times the atmospheric pool. This review synthesizes recent advances in understanding how land-use changes (conversion of forests/grasslands to cropland, urbanization, intensive agriculture, and restoration practices) alter microbial community composition, functional guilds, and biogeochemical processes. Key mechanisms include the soil microbial carbon pump (MCP), whereby labile plant inputs are transformed into stable microbial necromass and by-products that contribute disproportionately to persistent SOC, as well as shifts in fungal:bacterial ratios, extracellular enzyme activities, and microbial efficiency under varying management. Land conversion typically reduces microbial biomass, diversity, and carbon-use efficiency, accelerating SOC mineralization and nutrient loss, while conservation practices (no-till, cover cropping, agroforestry, organic amendments) enhance microbial necromass accumulation, mycorrhizal networks, and nutrient retention. Emerging evidence highlights the role of microbial residues in long-term stabilization, the sensitivity of keystone taxa to disturbance, and interactive effects with climate factors (warming, drought). The synthesis underscores that preserving or restoring microbial functional diversity is essential for enhancing SOC storage, improving nutrient-use efficiency, and building climate-resilient agroecosystems amid ongoing land-use intensification.